AN INDICATION OF AFRICAN CATFISH’S (CLARIAS GARIEPINUS) BEHAVIORAL CHANGES AS A RESPONSE FOR INCREASED SEISMIC ACTIVITY - Teuku Reza Ferasyi; Mustafa Sabri; Hamdani Hamdani; Azhari Azhari; Amiruddin Amiruddin; Erwin Erwin; Wolfgang Straka; Robert Faber (Universitas Syiah Kuala, 2013)
This report was aimed to describe the behavioral changes of catfish as observed before two different earthquakes hit the Province of Aceh, Indonesia in year of 2012. A number of 5 African’s catfish (Clarias gariepinus) were placed in an aquarium located in Gapang, Sukakarya Sub-district of Sabang Town, Aceh. Their behavior activities were observed manually at three different times (08.00 AM, 01.00 PM, and 05.00 PM) every day from 1st March up to 11th April 2012. The result of observation showed that the activity of catfish was different between all of them from 1st March 2012 up to morning observation on 11th April 2012. Most of those activities was not showed as very active behavior. However, their behavior was very active in the same pattern when observed at noon and afternoon times on 11 April 2012. On this date, there were two consecutive earthquakes happened at magnitude of 8 Richter Scale at 03.38 PM and 05.43 PM. The epicenter of this earthquake was in Simeulue, with the distance of more and less of 390 km from observation station of catfish in Gapang. It was noted that this abnormal behavior possibly showed as an indication of their ability to detect the increase of pre-seismic activity at 2.38 hours and 43 minutes before the two earthquakes. Perhaps, it is the result of their response to the increase of pre-seismic electromagnetic wave. Further continuous observation and research is needed to ensure the role of African’s catfish (Clarias gariepinus) as abio-sensor for the increase of seismic activity.